2008
DOI: 10.1111/j.1467-9701.2007.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

On Income Convergence among China, Hong Kong and Macau

Abstract: Hong Kong and Macau were reunited with China in the late 1990s as two special administrative regions (SARs). Over the last half century, they were China's good examples of economic development, windows of openness and investors. Owing to historical reasons, China lagged far behind Hong Kong and Macau in terms of per capita incomes. However, rapid economic growth in China over the last three decades must have brought about a significant convergence of the three economies. China's economic success has benefited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
3
1
1
Order By: Relevance
“…Panel data regression results indicate a convergence rate of 3.13 percent and a half-life accordingly reduced to 22.15 years. However, these results are significantly higher than those of previous studies on economic growth at the provincial level (Chen and Fleisher 1996;Ding and Haynes 2006;Gundlach 1997;Lei and Yao 2008). b Convergence Analysis over Different Time Periods Table 4 presents cross-sectional data regression results for absolute b convergence over three periods. Panel data regression results for each period are not presented because, in testing across multiple periods, we found that spatial panel data regression analyses are not applicable to short-term yearly analyses.…”
Section: Resultscontrasting
confidence: 78%
“…Panel data regression results indicate a convergence rate of 3.13 percent and a half-life accordingly reduced to 22.15 years. However, these results are significantly higher than those of previous studies on economic growth at the provincial level (Chen and Fleisher 1996;Ding and Haynes 2006;Gundlach 1997;Lei and Yao 2008). b Convergence Analysis over Different Time Periods Table 4 presents cross-sectional data regression results for absolute b convergence over three periods. Panel data regression results for each period are not presented because, in testing across multiple periods, we found that spatial panel data regression analyses are not applicable to short-term yearly analyses.…”
Section: Resultscontrasting
confidence: 78%
“…Based on the convergence regression proposed by Barro and Sala-i-Martin (1992), we establish a spatial panel Han-Philips linear dynamic regression modeling equation (3-1). As for robustness considerations, we follow the method of Lin and Liu (2003) and establish a panel data fixed-effect model in equation (3-2) to verify the relationship between market-oriented reform and the regional convergence of R&D efficiency.where Yit represents the growth rate in the R&D efficiency of the i-th region in the t-th year; Yi0 represents the initial R&D efficiency in different regions. I represents the identity matrix; ω is an n×n rank spatial weight matrix.…”
Section: Research Methodology and Datamentioning
confidence: 99%
“…Based on the convergence regression proposed by Barro and Sala-i-Martin (1992), we establish a spatial panel Han-Philips linear dynamic regression modeling equation (3-1). As for robustness considerations, we follow the method of Lin and Liu (2003) and establish a panel data fixed-effect model in equation (3-2) to verify the relationship between market-oriented reform and the regional convergence of R&D efficiency.…”
Section: 12mentioning
confidence: 99%
“…Diğer kısmı ise koşullu yakınsamanın olduğu sonucuna varmışlardır (Canevo & Marcet, 2000;Mathur, 2005;Wo Ho, 2006;Giudici & Mollick, 2007;Galvao & Gomes, 2007;Dawson & Sen, 2007;Pastor & Serrano, 2008;Masron & Yusop, 2008;Lei & Yao, 2008;Bianchi et.al., 2009;Apergis et.al., 2010). Bu çalışmalardan bir kısmı farklı ülke gruplarında mutlak yakınsama bulurken diğer gruplamalarda ise koşullu yakınsamayı bulmuşlardır.…”
Section: Literatür Taramasıunclassified